Corrosion of Anodized Titanium Alloys - Jáquez Muñoz, Jesús Manuel; Gaona Tiburcio, Citlalli; Méndez Ramírez, Ce Tochtli; Carrera Ramírez, Martha Guadalupe; Baltazar Zamora, Miguel Ángel; Santiago Hurtado, Griselda; Lara Banda, María del Refugio; Estupiñan López, Francisco Humberto; Nieves Mendoza, Demetrio; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2024)
Ti and Ti alloys are employed in demanding industries such as aerospace, automotive, biomedical, aeronautic, structural, naval, and chemical, thanks to their resistance to corrosion due to the formation of the TiO2 film on the surface. Diverse research has established that different corrosive media could attack the oxide layer. One way to generate a stable, compact, and continuous oxide film is through anodizing treatment. The efficiency of anodization depends on diverse factors such as the microstructure, chemical composition of alloys, pH of electrolyte, time, and temperature of anodizing. This review aims to examine the corrosion resistance of the anodized layer on Ti and Ti alloys, with different parameters. The discussion is centered on the influence of the different parameters and alloy properties in the effectivity of anodizing when they are characterized by electrochemical techniques while studying the behavior of oxide.